Microporous copper foil and preparation method thereof

By using 10-50nm microporous copper foil in lithium batteries, the dendrite problem caused by uneven coating of positive and negative electrode sheets in lithium batteries is solved, extending the battery life and increasing the number of cycles.

CN119221086APending Publication Date: 2024-12-31RONGENE NEW MATERIALS (BEIJING) TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411342725.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Uneven coating of the slurry of the positive and negative electrode sheets in lithium batteries causes lithium ions to deintercalate, form dendrites, shorten battery life and cause safety problems.

Method used

A method of preparing microporous copper foil is adopted. By forming micropores of 10-50nm on the copper foil, the electrolyte penetrates under low viscosity and low surface tension to avoid dendrites, and micropores are formed at the protrusions by electrolytic corrosion. The hole is controlled at 10-50nm.

Benefits of technology

It effectively avoids dendrite problems caused by uneven electrode coating, extends the battery life and increases the number of cycle charge and discharge times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221086A_ABST
    Figure CN119221086A_ABST
Patent Text Reader

Abstract

The invention provides a microporous copper foil and a preparation method thereof, and relates to the field of lithium batteries. On one hand, the embodiment of the invention provides the preparation method of the microporous copper foil, and the preparation method comprises the following steps: S1, preparing the copper foil with a micro-modeling structure; and S2, preparing an electrolyte, putting the copper foil in the electrolyte, and electrolyzing to enable the point of the convex part of the micro-modeling structure of the copper foil to discharge, so as to prepare the micropore. The copper foil prepared by the method is provided with micropores with the diameter of 10-50nm, when the copper foil is coated with a negative electrode material, negative electrode slurry cannot permeate from the micropores with the size, and after the copper foil is assembled into a battery, electrolyte is low in viscosity and small in surface tension and can permeate from the A surface of the copper foil to the B surface of the copper foil through the micropores; the ion diameter is less than 1nm, and a large number of ions can simultaneously pass through the aperture of 10-50nm, so that dendritic crystals can be prevented from being generated in the charging and discharging processes due to non-uniform coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a microporous copper foil and a preparation method thereof. Background Art

[0002] The negative electrode current collector of lithium-ion batteries is copper foil, and the positive electrode current collector is aluminum foil. The negative electrode material is coated on both sides of the copper foil, and the positive electrode material is coated on both sides of the aluminum foil. The positive and negative electrodes are separated by a diaphragm in the middle. In the actual production process, the slurry on the positive and negative electrode sheets is unevenly coated, resulting in uneven electrode slurries on the positive and negative electrode sheets, with more electrode slurry in the protruding parts and less electrode slurry in the concave parts. When the lithium battery is charged, the lithium ions in the electrode slurry are deintercalated from the positive electrode material and embedded into the negative electrode material through the diaphragm. The protruding part of the positive electrode sheet has more electrode slurry and provides more lithium ions. The corresponding negative electrode sheet cannot provide enough negative electrode material to absorb lithium ions at the protruding part of the positive electrode. These lithium ions that cannot be absorbed by the negative electrode material are deposited on the surface of the negative electrode to form dendrites, causing the battery life to decay rapidly. Dendrites piercing the diaphragm can also cause safety problems.

[0003] In order to solve a series of problems caused by uneven slurry coating, patent 201810703557.X discloses a method for preparing microporous copper foil for negative electrode of high-capacity lithium-ion battery, the preparation method includes an electrolytic cell provided on a raw foil machine frame, an anode plate in the electrolytic cell, the anode cell is connected to the positive electrode of the power supply through a copper bus, a cathode roller connected to the negative electrode of the power supply is provided above the anode cell, characterized in that the anode plate is densely covered with numerous needle points, and the resulting copper foil has a porosity of 20% and a pore diameter of 10um; in the actual production process, when the pore diameter of the copper foil micropores is ≥1um, when the electrode slurry is wet-coated, the solvent or glue in the slurry will flow through the micropores to the reverse side and stick to the coating roller, causing the coating machine to be unable to produce. Summary of the invention

[0004] The object of the present invention is to provide a microporous copper foil, which has micropores with a diameter of 10-50nm. When the copper foil is coated with a negative electrode material, the negative electrode slurry cannot penetrate from the micropores of this size. After the copper foil is assembled into a battery, the electrolyte has low viscosity and small surface tension, and can penetrate from the A side of the copper foil to the B side of the copper foil through the micropores; the ion diameter is less than 1nm, and the pore size of 10-50nm is sufficient for a large number of ions to pass through at the same time, which can avoid the generation of dendrites during charging and discharging due to uneven coating.

[0005] Another object of the present invention is to provide a method for preparing a microporous copper foil, which comprises preparing a raised and recessed microstructure on the copper foil, performing electrolytic corrosion in an electrolyte, discharging at the tip of the raised portion, preferentially losing copper ions, and then forming micropores at the raised portion, wherein the pore size of the micropores can be controlled to be 10-50 nm.

[0006] The present invention solves the technical problem by adopting the following technical solutions.

[0007] On the one hand, an embodiment of the present invention provides a method for preparing a microporous copper foil, comprising the following steps:

[0008] S1, preparation of copper foil with microstructure;

[0009] S2, preparing an electrolyte, placing the copper foil in the electrolyte, and electrolyzing the copper foil so that the tip of the protruding part of the micro-structure of the copper foil discharges, thereby forming micropores.

[0010] In some embodiments of the present invention, the micro-shaped structure comprises a plurality of protrusions and recesses, and the plurality of protrusions and the plurality of recesses are alternately and equidistantly distributed.

[0011] In some embodiments of the present invention, the microstructure on the copper foil is obtained by extrusion molding.

[0012] In some embodiments of the present invention, in step S2, the electrolyte includes water, CuSO4 and H2SO4, wherein the concentration of CuSO4 in the electrolyte is 200±20g / L, and the concentration of H2SO4 is 60±6g / L. Preferably, the concentration of CuSO4 in the electrolyte is 200g / L, and the concentration of H2SO4 is 60g / L.

[0013] In some embodiments of the present invention, in step S2, the electrolysis comprises:

[0014] An anode roller, a cathode roller, a reel and a reel are arranged in the electrolytic cell. One end of the copper foil is connected to the reel, and the other end is connected to the reel by passing through the anode roller. -5 A-8.7*10 -5 The copper foil was electrolyzed at a current of 1000 A and wound up at a speed of 2 m / min.

[0015] On the other hand, an embodiment of the present invention provides a microporous copper foil, which is prepared by the microporous copper foil preparation method.

[0016] In some embodiments of the present invention, the pore size of the micropores is 10-50 nm.

[0017] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0018] The microporous copper foil provided by the present invention has micropores with a diameter of 10-50nm. When the copper foil with micropores of this size is coated with electrode slurry, the electrode slurry will not pass through the micropores. However, after the copper foil is assembled into a battery and injected with electrolyte, the electrolyte has low viscosity and small surface tension, and can penetrate from the A side of the copper foil to the B side of the copper foil through the micropores; and the ion diameter is less than 1nm, and the pore size of 10-50nm is sufficient for a large number of ions to pass through at the same time. When the copper foil is used in a battery, the generation of dendrites on the electrode can be avoided, thereby extending the service life of the battery and increasing the number of battery charge and discharge cycles.

[0019] The preparation method provided by the present invention can discharge the copper foil with microstructure at the tip under electrolysis, lose copper ions, and then form micropores at the protrusions of the copper foil, and the pore size of the micropores is controlled to be 10-50nm by controlling the current and electrolysis time. The preparation method is simple and fast, and can quickly obtain microporous copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 A microscopic image of a copper foil with a micro-shaped structure used in an embodiment of the present invention;

[0022] Figure 2 A schematic diagram of an electrolytic cell for preparing micropores in an embodiment of the present invention;

[0023] Figure 3 A schematic diagram of the structure of a microporous copper foil provided by an embodiment of the present invention installed in a battery;

[0024] Figure 4 A simplified schematic diagram of a microporous copper foil provided by an embodiment of the present invention;

[0025] Figure 5 for Figure 4 A magnified schematic diagram of part A;

[0026] Figure 6 This is a schematic cross-sectional view of a microporous copper foil coated with electrode slurry according to an embodiment of the present invention;

[0027] Icons: 201-negative electrode sheet A side, 203-negative electrode sheet B side, 204-diaphragm, 205-positive electrode sheet A side, 206-aluminum foil, 207-positive electrode sheet B side, 208-slurry accumulation, 209-micropores, 300-negative electrode slurry, 401-protrusions, 402-depressions, 501-anode roller, 502-cathode roller, 503-unwinding shaft, 504-rewinding shaft, 505-copper foil recovery shaft, 506-microporous copper foil, 507-electrolyte, B-protrusion height, C-protrusion diameter, D-protrusion spacing, D1-slurry thickness on negative electrode sheet A side, D2-slurry thickness on negative electrode sheet B side, D3-slurry thickness at the bottom of the depression, D4-slurry thickness at the top of the protrusion. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0029] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0030] On the one hand, an embodiment of the present invention provides a method for preparing a microporous copper foil 506, comprising the following steps:

[0031] S1, preparation of copper foil with microstructure;

[0032] S2, preparing an electrolyte 507, placing the copper foil in the electrolyte 507, and electrolyzing the copper foil so that the tip of the protrusion 401 of the micro-structure of the copper foil discharges, thereby forming micropores 209.

[0033] In some embodiments of the present invention, the micro-shaped structure comprises a plurality of protrusions 401 and depressions 402, and the plurality of protrusions 401 and the plurality of depressions 402 are alternately and equidistantly distributed. Figure 1 , 4 As shown in Figure 6, the micro-structure on the copper foil has protrusions 401 and depressions 402 (seen from one side), and the protrusions 401 and the depressions 402 are arranged alternately, one column of protrusions 401 and one column of depressions 402, and the columns of protrusions 401 and the columns of depressions 402 are arranged alternately. Specifically, in the embodiment provided by the present invention, the thickness of the copper foil is 8um, and the spacing between two columns of protrusions 401 or adjacent protrusions 401 is 140um.

[0034] It should be noted that the principle of preparing the micropores 209 by tip discharge in the present invention is as follows:

[0035] When the micro-shaped copper foil passes through the anode roller 501, due to the tip effect, the copper atoms at the top are electrolyzed first, and the copper atoms lose two electrons and are converted into copper ions that enter the electrolyte, thereby corroding micropores 209 at the tip.

[0036] In some embodiments of the present invention, the microstructure on the copper foil is obtained by extrusion molding. Specifically, a laser is first used to micro-shape the copper foil on a steel roller with a diameter of φ50mm-2000mm and a length of 100mm-2000mm. Two micro-shaped steel rollers are used. The steel rollers after micro-shaping are called forming devices. The forming devices are then installed on a rolling mill. The copper foil passes between the forming devices, the gap between the upper and lower forming devices is adjusted, and pressure is applied to the forming device to copy the surface shape of the forming device onto the copper foil. After extrusion molding, the micro-shaped copper foil of the present invention is obtained.

[0037] In some embodiments of the present invention, in step S2, the electrolyte 507 includes water, Cu S O4 and H2SO4, wherein the concentration of CuSO4 in the electrolyte 507 is 200g / L and the concentration of H2SO4 is 60g / L.

[0038] In some embodiments of the present invention, in step S2, the electrolysis comprises:

[0039] An anode roller 501, a cathode roller 502, a reel 503 and a reel 504 are arranged in the electrolytic cell. One end of the copper foil is connected to the reel 503, and the other end is connected to the reel 504 by passing through the anode roller 501. The anode roller 501 is connected to the positive electrode of the power supply, and the cathode roller 502 is connected to the negative electrode of the power supply. -5 A-8.7*10 -5 A current, and the copper foil is rolled up at a speed of 2m / min. Figure 2 The micro-shaped copper foil is unwound from the unwinding reel 503, passes around the anode roller 501, and is rolled up on the reel 504 to obtain the microporous copper foil 506. The tip of the protrusion 401 of the micro-shaped copper foil will be electrolyzed to ionize copper ions. The copper foil with copper ions deposited on the cathode roller 502 is rolled up and recycled by the copper foil recycling reel 505.

[0040] The micro-shaped copper foil has a width of 300 mm, a thickness of 8 μm, a protrusion spacing D of 140 μm, and protrusions 401 and depressions 402 are alternately and equidistantly distributed. According to calculations, when a 10 nm aperture is required on the top of each protrusion 401, the amount of electricity released by 1 m2 of micro-shaped copper foil is 1.74*10 -3 Coulomb, the area of ​​foil flowing through the electrolytic cell in 1S is 0.01m 2 , the amount of electricity that can be released is 1.74*10 -5Coulomb, the electrolysis current is set to 1.74*10 -5 A;

[0041] The micro-shaped copper foil has a width of 300mm, a thickness of 8um, a protrusion spacing D of 140um, and protrusions 401 and recesses 402 are alternately and equidistantly distributed. After calculation: when a 50nm aperture is required on the top of each protrusion 401, 1m 2 The amount of electricity released by the micro-shaped copper foil is 8.7*10 -3 Coulomb, the area of ​​foil flowing through the electrolytic cell in 1S is 0.01m 2 , the amount of electricity that can be released is 8.7*10 -5 Coulomb, the electrolysis current is set to 8.7*10 -5 A;

[0042] The diameter of the micropores 209 of the copper foil prepared by the above method is 10-50 nm.

[0043] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0044] Example 1

[0045] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 1.74*10 -5 A.

[0046] Example 2

[0047] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 3.48*10 -5 A.

[0048] Example 3

[0049] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 5.22*10 -5 A.

[0050] Embodiment 4:

[0051] A micro-shaped copper foil substrate was selected: width 300 mm, protrusion height B 12 um, protrusion diameter C 6 um, protrusion spacing D 140 um, and electrolysis was carried out in an electrolytic cell. During electrolysis, the substrate winding speed was 2 m / min, and the electrolysis current was 6.96*10-5A.

[0052] Embodiment 5:

[0053] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 8.7*10 -5 A.

[0054] Comparative Example 1:

[0055] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 1.74*10 -6 A.

[0056] Comparative Example 2:

[0057] Select the micro-shaped copper foil substrate: width 300mm, convex height B12um, convex diameter C 6um, convex spacing D140um, electrolyze in the electrolytic cell, substrate winding speed 2m / min, electrolysis current 1.74*10 -3 A.

[0058] Effect example

[0059] A. Lithium battery electrolyte permeability test

[0060] Use a pipette to suck up the electrolyte of the lithium battery and drop it on the upper surface of the microporous copper foil 506, stick a piece of pH test paper on the lower surface of the microporous copper foil 506, and observe the color change time of the pH test paper.

[0061] B. Slurry permeability test

[0062] Weigh 95.1 g of graphite, 1 g of carbon black, 1.6 g of CMC, 2.3 g of SBR (4.6 g of emulsion), and 120 g of water, stir for 3 h, and prepare a negative electrode slurry 300.

[0063] Use a small spoon to transfer 1 spoon of slurry to the upper surface of the microporous copper foil 506, and stick a piece of pH test paper on the lower surface of the microporous copper foil 506 to observe the color change time of the pH test paper.

[0064] C. Tensile strength test

[0065] Use a sampler to cut a microporous copper foil 506 with a length*width of 100*25mm, and conduct a room temperature tensile mechanical properties test. The gauge length is 50mm, the test rate is 5mm / min, and the tensile strength is recorded.

[0066] The results are shown in Table 1

[0067] Table 1 Microporous copper foil properties of Examples 1-5 and Comparative Examples 1-2

[0068]

[0069]

[0070] From the results of Example 1 to Example 5, as the electrolysis current increases, the time for the lithium battery electrolyte to penetrate the microporous copper foil 506 becomes shorter and shorter, indicating that the pore size of the micropores 209 is getting larger and larger; and the slurry cannot penetrate the microporous copper foil; the tensile strength has no obvious change;

[0071] Comparative Example 1 has too small electrolytic current, and the micropores 209 are too small, and thus do not have the characteristics of microporous copper foil;

[0072] In Comparative Example 2, the electrolysis current is too large, the micropores 209 are too large, and the slurry will penetrate through the microporous copper foil 506, which is not suitable for large-scale coating production.

[0073] As attached Figure 6 As shown, the top of the protrusion 401 of the microporous copper foil 506 is in a through-hole state, namely, the micropore 209. After the negative electrode material is coated on both sides of the microporous copper foil 506, the amount of negative electrode material at D1 and D2 is relatively balanced; the coating amount at D3 and D4 is unbalanced, and the amount of negative electrode material at D3 is more than that at D4. When the battery is charged and discharged, the negative electrode material at D4 cannot fully absorb the lithium ions migrated from the positive electrode sheet, but the excess lithium ions will pass through the through-hole and recombine with the negative electrode material at D3; when the positive electrode sheet is unevenly coated, the excess lithium ions will also pass through the micropore 209 to prevent lithium precipitation and the formation of dendrites.

[0074] When the electrode slurry is unevenly coated on the electrode surface, such as Figure 3 The two sides of the microporous copper foil 506 are coated with negative electrode materials, and the two sides of the aluminum foil are coated with positive electrode materials. The positive and negative electrode sheets are separated by a diaphragm in the middle. In the actual production process, the coating is uneven. Figure 3 It can be seen visually that there is a bulge in the coating on the positive electrode surface 205, which is the pile 208 caused by uneven coating. During charging, lithium ions are deintercalated from the positive electrode material and embedded into the negative electrode material through the diaphragm. When the negative electrode surface 203 cannot provide enough negative electrode material to absorb the lithium ions deintercalated from the positive electrode surface 205, the lithium ions will pass through the micropores 209 on the copper foil and embed into the negative electrode material on the negative electrode surface A, thus avoiding the formation of dendrites.

[0075] In summary, the microporous copper foil provided by the present invention has micropores with a diameter of 10-50nm. When the copper foil with micropores of this size is coated with electrode slurry, the electrode slurry will not pass through the micropores. However, after it is assembled into a battery and injected with electrolyte, the electrolyte has low viscosity and small surface tension, and can penetrate from the A side of the copper foil to the B side of the copper foil through the micropores; and the ion diameter is less than 1nm, and the pore size of 10-50nm is sufficient for a large number of ions to pass through at the same time. Applying it in a battery can avoid the formation of dendrites on the electrode, thereby extending the service life of the battery and increasing the number of battery charge and discharge cycles.

[0076] The preparation method provided by the present invention can discharge the copper foil with microstructure at the tip under electrolysis, lose copper ions, and then form micropores at the protrusions of the copper foil, and the pore size of the micropores is controlled to be 10-50nm by controlling the current and electrolysis time. The preparation method is simple and fast, and can quickly obtain microporous copper foil.

[0077] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a microporous copper foil, characterized in that: The following steps are involved: S1, preparation of copper foil with microstructure; S2, preparing an electrolyte, placing the copper foil in the electrolyte, and electrolyzing the copper foil so that the tip of the protruding part of the micro-structure of the copper foil discharges, thereby forming micropores.

2. The method for preparing a microporous copper foil according to claim 1, characterized in that: The micro-modeling structure includes a plurality of protrusions and recesses, and the plurality of protrusions and the plurality of recesses are alternately and equidistantly distributed.

3. The method for preparing a microporous copper foil according to claim 1, characterized in that: The microstructure on the copper foil is obtained by extrusion molding.

4. The method for preparing a microporous copper foil according to claim 1, characterized in that: In step S2, the electrolyte includes water, CuSO4 and H2SO4, wherein the concentration of CuSO4 in the electrolyte is 200 g / L and the concentration of H2SO4 is 60 g / L.

5. The method for preparing a microporous copper foil according to claim 1, characterized in that: In the step S2, the electrolysis comprises: An anode roller, a cathode roller, a reel and a reel are arranged in the electrolytic cell. One end of the copper foil is connected to the reel, and the other end is connected to the reel by passing through the anode roller. -5 A-8.7*10 -5 The copper foil was electrolyzed at a current of 1000 A and wound up at a speed of 2 m / min.

6. A microporous copper foil, characterized in that: The microporous copper foil is prepared by the method for preparing the microporous copper foil according to any one of claims 1 to 5.

7. The microporous copper foil according to claim 6, characterized in that: The pore size of the micropores is 10-50 nm.

Citation Information

Cited By

  • Battery cell structure of solid-state battery, solid-state battery, battery manufacturing equipment and battery manufacturing process

    CN120767286A